1897 Id. Sess. Laws 89, § 2, pt. 18 - (:unkn) unknown (General Publisher, 1897)
Amended the Boise city charter to authorize the storage and sale of gun powder and other combustible materials, as well as "all possible and proper means" to prevent the daner or risky of injury or damage by fire from carelessness, negligence, or otherwise.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER